Pengendalian Kualitas Produk Keripik Tempe di IKM Sido Mukti dengan Pendekatan DMAIC Six Sigma - Riestika Nur Insani Putri,; Rossy Septy Wahyuni, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Quality control is crucial for industry, including small businesses like Sido Mukti Small and Medium Enterprises (SMEs), a tempeh chip producer. Lack of proper quality control results in defective products. Although the sigma level remained at 6 before and after improvements, the sigma value increased from 2.77 to 3.26 after several changes were made. Production issues identified included the absence of clear inspection standards, no time guidelines, poor machine maintenance, reliance on manual tools prone to human error, unclean soybean washing, the absence of standardized yeast dosages, inadequate record-keeping, open storage, and unstable weather conditions. Recommended improvements include establishing inspection, time, and maintenance standards, purchasing better machinery and scales, standardizing yeast dosages, record-keeping, maintaining a clean fermentation area, and managing weather conditions.